The Effect of Buzz Group Modification Method on Exclusive Breastfeeding Against Self Efficacy in Pregnant Women: A Quasi Experiment (Medico Legal Update, 2020)
Background: Exclusive breastfeeding for six months is an effort to increase the breastfeeding benefits andreduce infant mortality rate. Self efficacy is one of the factors that can influence the level of confidenceexclusive in breastfeeding.Aim: This study aimed to identify the level of self efficacy before and after given modified buzz groupmethod and to the influence of modified buzz group method about exclusive breastfeeding against selfefficacy in pregnant motherMethod: This study was designed using quasi-experimental design. The study was conducted in the workingarea of the health center. The total population used in this study was 42 pregnant women. A total sample of38 respondents was taken according to purposive sampling. BSES-SF (Breastfeeding Self Efficacy ScaleShort Form) questionnaire was administered at pre-test and post-test. Data analysis was performed using theWilcoxon Signed Rank test and the Mann Whitney test.Results: The results showed that the Wilcoxon Signed Rank statistical test obtained p value of 0,000 inthe treatment group and p value of 0.355 in the control group. The Mann Whitney statistical test obtaineda significant value of p = 0,000 at the post-test. The modification of the buzz group method took effectto increased self efficacy about exclusive breastfeeding for pregnant mother because this method wasorganized by four sources of self efficacy that was direct experience, indirect experience, verbal persuasion,and emotional condition.Conclusion: With the modification of the buzz group method and self efficacy for pregnant mother canincrease of value for breastfeeding exclusive coverage.